국내 하천/호수에 적용된 조류저감기술의 조사 및 평가 - 변규덕(Kyu Deok Byeon); 김가영(Ga Young Kim); 이인주(Inju Lee); 이새로미(Saeromi Lee); 박재로(Jaeroh Park); 황태문(Taemun Hwang); 주진철(Jin Chul Joo) (Daehan hwan'gyeong gonghag hoeji, 2016)
Commercial 28 algae removal technologies that have been applied in domestic rivers and lakes with green tide were investigated, analyzed and classified. The classification of algae removal technologies was based on the three criteria (i.e., principle, flow rate of water body, and application period). Also, algae removal technologies were evaluated in terms of cost effectiveness, field applicability, effect durability, and eco friendliness. From the analysis results, technologies using physical, chemical, biological, and convergent controls were 32.2%, 25%, 21.4%, and 21.4%, respectively. The 75% of technologies have been applied to stagnant water body (${≤}0.2m/s$). Also, algae harvesting ship with dissolved air flotation, conveyor belt and filtration processes and natural floating coagulant were found to have better field applicability, compared to other technologies. However, proper algae removal technology in specific rivers and lakes should be chosen after the evaluation of long-term pilot scale field test. Also, development of energy and resource recovery technologies from algae biomass is warranted. 실제 하천과 호소에서 적용된 상용화된 28개 조류저감기술의 현장적용 자료를 조사하고, 이를 평가(evaluation) 분석(analysis)하여 분류(classification)하였다. 분류 기준은 공법구분, 적용 수체의 유속, 적용 시점의 3가지 기준에 의해 분류하였으며, 각 조류저감기술은 경제성, 현장 적용성, 효과 지속성, 수생태 안전성을 기준으로 평가를 실시하였다. 공법 원리별로 분류시 물리적 공법이 32.2%, 화학적 공법이 25%, 생물학적 공법이 21.4%, 복합처리 공법이 21.4%를 차지하였다. 조사된 조류저감기술의 75%는 유속 0.2 m/s 이하의 정체된 호소, 저수지, 소형 하천을 대상으로 적용되었다. 가압부상장치와 컨베이어 벨트 및 탈수장치를 탑재한 이동식 녹조제거선과 광물기반 천연 부유응집제 기술이 타 기술 대비 현장 적용성은 우수한 것으로 조사되었다. 발생현장에 적합한(site-specific) 맞춤형 조류저감기술의 도입은 pilot 규모의 장 단기 운전을 통해 효율을 검증 후 최종 도입하는 것이 바람직하다. 또한, 회수된 조류 바이오매스를 생물 자원화를 통해 에너지 회수형 조류저감기술 등의 신속한 개발 및 보급이 필요하다.